A CONTENT ANALYSIS OF ”I LOVE JAKARTA 6” ENGLISH TEXTBOOK - Afifah Luthfiyyah; Evi Karlina Ambarwati (IKIP Siliwangi, 2023)
The aim of the study was to evaluate the quality of EFL Textbook for students elementary school in Jakarta based on criteria from Badan Standar Nasional Pendidikan (BNSP) in term of materials, language, presentation of materials and grapics aspecs. The research used qualitative approach.by employing content analysis. The instrument was checklist observation based on BNSP criteria. The researcher found that language-related qualities, the presentation, and the graphics all met the criteria. Unfortunately, there were few grammatical errors in the materials. In general the book met the national standard, although improvement regarding grammar is required. Keywords: English Textbook; Content Analysis; Elementary School